KEWENANGAN LEMBAGA ATAU PEMANGKU ADAT DESA SAUSU PEORE, KABUPATEN PARIGI MOUTONG DALAM PELAKSANAAN PERKAWINAN POLIGAMI - I Gede Deva Adnyana; Rosnani Lakunna; Dewi Kemala Sari (The Juris, 2026)
This study aims to analyze the authority of customary institutions and traditional leaders in Sausu Peore Village, Parigi Moutong Regency, in the implementation of polygamous marriages under Balinese customary law and its relationship with Indonesian national law. This research employed an empirical juridical method using statutory and socio-legal approaches. Primary data were collected through interviews with customary leaders and representatives of the Indonesian Hindu Council (Parisada Hindu Dharma Indonesia/PHDI), while secondary data were obtained from legislation, books, and scientific journals. The findings reveal that customary leaders have the authority to validate the implementation of polygamous marriages based on Balinese customary law by ensuring compliance with Hindu religious teachings, obtaining the consent of the parties involved, and conducting the required customary ceremonies. Customary institutions are also authorized to regulate marriage procedures, provide guidance, and reprimand or reject marriage ceremonies that do not comply with customary and religious requirements. Nevertheless, the implementation of polygamous marriages must also fulfill the legal requirements stipulated in Law Number 1 of 1974 on Marriage to obtain recognition under national law. Therefore, the authority of customary institutions serves as a complementary mechanism to national law by regulating the social, cultural, and religious aspects of marriage within the Balinese customary community in Sausu Peore Village.